The phenotypic spectrum of duplication 5q35.2–q35.3 encompassing NSD1: Is it really a reversed sotos syndrome?. Issue 9 (2nd August 2013) - Dikow, Nicola; Maas, Bianca; Gaspar, Harald; Kreiss‐Nachtsheim, Martina; Engels, Hartmut; Kuechler, Alma; Garbes, Lutz; Netzer, Christian; Neuhann, Teresa M.; Koehler, Udo; Casteels, Kristina; Devriendt, Koen; et al.
Abstract Loss‐of‐function mutations of NSD1 and 5q35 microdeletions encompassing NSD1 are a major cause of Sotos syndrome (Sos), which is characterized by overgrowth, macrocephaly, characteristic facies, and variable intellectual disability (ID). Microduplications of 5q35.2–q35.3 including NSD1 have been reported in only five patients so far and described clinically as a reversed Sos resulting from a hypothetical gene dosage effect of NSD1. Here, we report on nine patients from five families with interstitial duplication 5q35 including NSD1 detected by molecular karyotyping. The clinical features of all 14 individuals are reviewed. Patients with microduplications including NSD1 appear to have a consistent phenotype consisting of short stature, microcephaly, learning disability or mild to moderate ID, and distinctive facial features comprising periorbital fullness, short palpebral fissures, a long nose with broad or long nasal tip, a smooth philtrum and a thin upper lip vermilion. Behavioral problems, ocular and minor hand anomalies may be associated. Based on our findings, we discuss the possible etiology and conclude that it is possible, but so far unproven, that a gene dosage effect of NSD1 may be the major cause. © 2013 Wiley Periodicals, Inc.